Intervention or phasal locality? Two ways of being local in French causative constructions - Rouveret, Alain (Romance Languages and Linguistic Theory 10: Selected papers from 'Going Romance' 28, Lisbon, 2016)
The Minimalist Program claims that only two notions of locality are necessary: phasal locality and intervention locality (in the form of the Minimal Link Condition). This paper asks whether the unification of the two is possible or desirable. An argument against unification would consist in showing that a process A obeys one locality condition and doesn’t obey the other and that another process B does exactly the reverse. Two phenomena are considered, which fit this description – respectively interpretation (R-I) and clitic placement (CL-PL). Their contrasting behavior in the French faire-construction indicates that each one obeys a locality condition that the other does not: CL-PL obeys phasal locality, R-I some form of minimality. The theoretical implications of these findings for the theory of locality and the architecture of grammar are examined in the conclusion.
Keywords: Agree; Applicative head; Clitic Placement; Faire-construction; intervention; locality; Object Shift; phases; Quantifier Raising; Subject Raising